A facile synthesis of Fe3O4@SiO2@ZnO with superior photocatalytic performance of 4-nitrophenol. Issue 3 (June 2017) - Qin, Yuelong; Zhang, Hanbing; Tong, Zhangfa; Song, Zhenyu; Chen, Ninghua
Graphical abstract: Highlights: ZnO MNPs were synthesized by a moderate and rapid route. Enhanced photocatalytic performance of ZnO MNPs for 4-NP was observed. The good reusability of ZnO MNPs has been verified by eight times repetitive runs. Abstract: Nitrophenols in wastewater have posed a serious threat to ecosystem and human health, hence it is very important to remove them from wastewater using an environmental-friendly and effective method. In this study, Fe3 O4 @SiO2 @ZnO magnetic nanoparticles (ZnO MNPs) were synthesized via a moderate and rapid route using microwave irradiation and diethylene glycol (DEG) as solvent. The facile synthesis conditions of ZnO nanoparticles coating on Fe3 O4 @SiO2 were confirmed owing to lower reaction temperature (160 °C) and quick reaction time (15 min microwave irradiation). In addition, the synthesized ZnO MNPs demonstrated the comparable or even better photocatalytic activity for 4-nitrophenol (4-NP) as compared with TiO2 with respect to small catalyst dosage, quick degradation rate and broad pH range. Moreover, ZnO MNPs exhibited good stability and reusability after eight times successive degradation experiments of 4-NP. The mechanism of the enhanced photocatalytic activity of ZnO MNPs was mainly related to the stronger adsorption ability for 4-NP, the improved light absorption ability and the retarding recombination of hole–electron pairs. In summary, ZnO MNPs is a promising candidate for 4-NP photocatalytic degradation from wastewater.